Robust methods in univariate time series models - Whitehouse, Emily J. (2017)
The size and power properties of a hypothesis test typically depend on a series of factors which are unobservable in practice. A branch of the econometric literature therefore considers robust testing methodologies that achieve good size-control and competitive power across a range of differing circumstances. In this thesis we discuss robust tests in three areas of time series econometrics: detection of explosive processes, unit root testing against nonlinear alternatives, and forecast evaluation in small samples.